HUSBAND'S SUPPORT AND PARITIES WITH SELECTION OF INJECTED CONTRACEPTION OF KB ACCEPTORS IN PUSKESMAS BALOI PERMAI - Luis Luis Yulia; Bratasena Bratasena (Universitas Batam, 2020)
Background : The increasing number of Indonesia's population is the impact of increasing birth rates. KB Injection is the most widely used family planning by women of reproductive age (WUS). The height of the 3-month injection family planning acceptors is influenced by several factors, namely age, education, occupation, income, and parietas. The purpose of this study was to determine the relationship between husband and parietas support with the choice of injection contraception. Method : The research method is analytical survey with cross sectional approach. Conducted at the Baloi Permai puskesmas, the study was conducted for 6 months, the population in this study were all injection family planning acceptors in the working area of the Baloi Pemai Puskesmas as many as 6,219 acceptors. With a sample size of 98 people, sampling using purposive sample with research instruments using a questionnaire and analyzed using Chi Square. Result : The results of the parity study of acceptors who chose the most injection contraceptive were the category of children 2-4 years as many as 57 people (58.2%). Contraceptive family planning acceptors who chose injection contraceptives the most were injection contraceptives for 3 months as many as 51 respondents (52.0%). with a p value = 0.025. Conclusion : Suggestions for agat acceptors can find out the advantages and disadvantages of contraceptives to be used and should ask for an explanation from health workers to provide assistance in choosing contraceptives so that the family planning used is truly safe to use even in the long term